The newly discovered glymphatic system: the missing link between physical exercise and brain health? - Olegário, Raphael Lopes; Nóbrega, Otávio Toledo; Camargos, Einstein Francisco (Frontiers in Integrative Neuroscience, 2024)
Dementias are responsible for the most frequent neurodegenerative diseases and the seventh leading cause of death worldwide. As a result, there is a growing effort by the neuroscientific community to understand the physiopathology of neurodegenerative diseases, including how to alleviate the effects of the cognitive decline by means of non-pharmacological therapies (e.g., physical exercise). Studies have shown that exercise can improve aspects of brain health related to cognition. However, there still needs to be more knowledge regarding the mechanisms controlling these relationships, and a newly discovered cleansing system in the brain, named the glymphatic system, can be the missing link in this mechanism. The objective of this paper is to review recent findings regarding the potential impacts of physical exercise on the glymphatic system and its implications for the onset of neurodegenerative diseases. Additionally, considering the close interplay between exercise and sleep quality, we aim to explore how sleep patterns may intersect with exercise-induced effects on glymphatic function, further elucidating the complex relationship between lifestyle factors and brain health.